Probabilitas Perpindahan Pengguna Moda Transportasi dari Kendaraan Pribadi ke Biskita Trans Pakuan - Hasna Nisrina Pribadi; Eva Azhra Latifa (Jurnal Poli-Teknologi, 2025)
The Jabodetabek Transportation Management Agency (BPTJ) launched the Biskita Trans Pakuan in the city of Bogor with a subsidy based on the Buy the Service (BTS) scheme, which complies with the established Minimum Service Standards. This scheme requires transport operators to provide the best service so that private vehicle users are expected to switch to public transportation The Biskita route with corridor number K2 runs between the Bubulak and Sindangsari Terminals, previously a busy route with no public transportation. This caused congestion during rush hour due to two- wheeled and four-wheeled private vehicles filling the road. This study aims to address these problems by analyzing the characteristics of travelers, assessing the potential shift from private vehicle users to Biskita Trans Pakuan, and providing recommended solutions from respondents. Data was collected by distributing a questionnaire via Google Forms using the Stated Preference technique and analyzed using Multiple Linear Regression to Probability Method. The variables examined were cost, time, and service. A total of 72% of respondents were private vehicle users and 28% were Biskita users. Based on the analysis results, the majority of respondents were women, aged 20–25 years and over 40 years, students, university students, and private employees, with a monthly income of IDR 500,001–4,500,000 and transportation costs of more than IDR 200,000. The majority of trips originated from Bubulak Terminal and were destined for Bogor Station/Bogor City Square, for purposes such as education, work, and recreation. Based on statistical testing, 11.4% of respondents were willing to switch to Biskita Trans Pakuan if there were no changes in cost, time, or service expectations. Based on respondent recommendations, optimizing Biskita services can be done by increasing the number of buses (30%), improving service quality (20%), adding routes (18%), adding stops (16%), and extending operational hours (16%).